Lysophosphatidic Acid Enhances In Vivo Infiltration and Activation of Guinea Pig Eosinophils and Neutrophils via a Rho/Rho-Associated Protein Kinase-Mediated Pathway - Terumasa Hashimoto; Miyuki Yamashita; Hisayuki Ohata; Kazutaka Momose (Elsevier, 2003)
Lysophosphatidic acid (LPA) has been shown to be a chemoattractant in in vitro studies. The present study was carried out to determine whether LPA enhances infiltration of inflammatory cells in in vivo studies with guinea pigs. LPA (1 - 10 μg/ml), when by guinea pigs for 5 min, substantially increased the numbers of eosinophils and neutrophils in the bronchoalveolar lavege fluid (BALF), which was recovered at over 4 h after the inhalation of LPA. Infiltration in BALF was significantly inhibited by inhalation of Y-27632, an inhibitor of Rho-associated protein kinase (ROCK). LPA also increased superoxide production of eosinophils and neutrophils. In contrast, Y-27632 inhibited superoxide production. These findings suggest that LPA may contribute to infiltration and activation of inflammatory cells in bronchial asthma; furthermore, the Rho/ROCK-mediated pathway may be involved.